2023
DOI: 10.3390/ijms24065220
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Endocannabinoids as Key Lipid Mediators for a Successful Pregnancy

Abstract: In recent years, Cannabis use/misuse for treating pregnancy-related symptoms and other chronic conditions has increased among pregnant women, favored by decriminalization and/or legalization of its recreational uses in addition to its easy accessibility. However, there is evidence that prenatal Cannabis exposure might have adverse consequences on pregnancy progression and a deleterious impact on proper neurodevelopmental trajectories in the offspring. Maternal Cannabis use could interfere with the complex and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 255 publications
0
0
0
Order By: Relevance
“…For instance, the sharp increase in CB 1 during adulthood correlates to its functional endometrial role during the preimplantation stage [27]. Moreover, the modulation of NAPE-PLD, FAAH, and DAGL-α is consistent with accumulated literature data that show a key role of eCBs in the regulation of several steps during the estrous/menstrual cycle [4,28], as well as during early and late stages of pregnancy [29,30] in several mammalian species. Interestingly, the tissue localization of both NAPE-PLD and FAAH in the oviducts and uteri appears mainly in the epithelial cells facing the lumen of the organ, or glandular cells, as also reported in other species [28,29,31,32].…”
Section: Discussionsupporting
confidence: 86%
“…For instance, the sharp increase in CB 1 during adulthood correlates to its functional endometrial role during the preimplantation stage [27]. Moreover, the modulation of NAPE-PLD, FAAH, and DAGL-α is consistent with accumulated literature data that show a key role of eCBs in the regulation of several steps during the estrous/menstrual cycle [4,28], as well as during early and late stages of pregnancy [29,30] in several mammalian species. Interestingly, the tissue localization of both NAPE-PLD and FAAH in the oviducts and uteri appears mainly in the epithelial cells facing the lumen of the organ, or glandular cells, as also reported in other species [28,29,31,32].…”
Section: Discussionsupporting
confidence: 86%
“…Prolonged endocannabinoid signaling is linked to adverse pregnancy outcomes (78). Bariani et al (8) found that LPS altered AEA and related endocannabinoid-like lipid levels in the uterus, consistent with previous research (75,76). LPS-induced cytokines can affect endocannabinoid production by modulating the expression and activity of fatty acid amide hydrolase (FAAH) (79,80).…”
Section: Mechanisms Of Action: Resveratrol Targeting the Mechanism Of...mentioning
confidence: 53%
“…With the rise in cannabis consumption among reproductive age-women, and the increase in THC potency within cannabis preparation, it is important to further investigate how THC may interact with the ECS within the female reproductive system. The ECS has a prominent role in mammalian reproduction and is present in all female reproductive tissues [ 15 , 33 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…THC can directly modulate the ECS, which has been detected throughout the female reproductive system including the placenta, uterus, endometrium, ovary, embryo, oocyte, follicular fluid and granulosa cells (GCs) [ 15 , 37 40 ]. The ECS controls various aspects of reproduction, including the release of gonadotropins, steroid hormone synthesis, the production and release of male and female gametes, and pregnancy [ 15 , 41 ].…”
Section: Introductionmentioning
confidence: 99%